Hubungan karakteristik individu, gejala kelelahan subjektif, kompetensi, persepsi ketersediaan alat pelindung diri terhadap kecelakaan kerja pekerja Mechanical Electrical Plumbing (MEP) - Maharani, Nabila; Setyaningsih, Yuliani; Widjasena, Baju (Talenta Publisher, 2023)
A work accident is an unexpected event that can cause human casualties and property damage. According to data from the Ministry of PUPR in 2017, many work accidents occurred in the construction sector. Thus, Occupational Safety and Health are needed by construction sector workers in minimizing the occurrence of work accidents. Analyzing the relationship between characteristics, subjective fatigue symptoms, competence, and perceptions of PPE availability on the incidence of work accidents in MEP Construction Project PT. X, Jakarta. Quantitative with cross sectional design. The sample size was 68 people using the total sampling method which was then analyzed by chi-square statistical analysis. The results of the bivariate analysis in this study indicate that there is a relationship between age, length of service, subjective fatigue symptoms, competence, and perceptions of PPE availability to work accidents. But there is no relationship between the type of work on work accidents. To minimize the occurrence of work accidents, management is expected to improve the quality of workers by conducting training for workers and optimizing the K3 program.